How do earthquakes shape economic behavior? - Chen, Kevin Z.; Filipski, Mateusz J.; Zhang, Xiaobo (2019)
Research shows how a disaster can impact an economy beyond the simple rebuilding process. The Sichuan earthquake induced a lifestyle shift in households toward greater spending and a structural shift of the economy away from industrial production.